2006
DOI: 10.1007/s10801-006-8346-x
|View full text |Cite
|
Sign up to set email alerts
|

Pointed and multi-pointed partitions of type A and B

Abstract: 21 pages, 3 figures.International audienceThe aim of this paper is to define and study pointed and multi-pointed partition posets of type A and B (in the classification of Coxeter groups). We compute their characteristic polynomials, incidence Hopf algebras and homology groups. As a corollary, we get that some operads are Koszul over Z. Cet article introduit et etudie les posets des partitions pointees et multi-pointees en type A et B (dans la classification des groupes de Coxeter finis). Leurs polynomes carac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 12 publications
0
30
0
5
Order By: Relevance
“…We refer the reader to the article [6] of Chapoton and the author for a study of the properties of the pointed partition posets.…”
Section: Homology Of the Poset π Pmentioning
confidence: 99%
See 3 more Smart Citations
“…We refer the reader to the article [6] of Chapoton and the author for a study of the properties of the pointed partition posets.…”
Section: Homology Of the Poset π Pmentioning
confidence: 99%
“…In [6], we have shown that the posets of multi-pointed partitions are totally semi-modular. Therefore, they are Cohen-Macaulay and we have the following theorem.…”
Section: The Posets π Mp Of Multi-pointed Partitionsmentioning
confidence: 99%
See 2 more Smart Citations
“…On peut obtenir une preuve plus courte de cette proposition en utilisant les résultats de [7] et les méthodes de [20] qui donnent un description du complexe d'ordre de chaque intervalle dans le poset des partitions pointées.…”
Section: Donc On a Obtenuunclassified